Second-generation colon capsule endoscopy for detection of colorectal polyps: Systematic review and meta-analysis of clinical trials - Möllers, Tobias; Schwab, Matthias; Gildein, Lisa; Hoffmeister, Michael; Albert, Jörg; Brenner, Hermann; Jäger, Simon (Endoscopy International Open, 2021)
Background and study aims Adherence to colorectal cancer (CRC) screening is still unsatisfactory in many countries, thereby limiting prevention of CRC. Colon capsule endoscopy (CCE), a minimally invasive procedure, could be an alternative to fecal immunochemical tests or optical colonoscopy for CRC screening, and might increase adherence in CRC screening. This systematic review and meta-analysis evaluates the diagnostic accuracy of CCE compared to optical colonoscopy (OC) as the gold standard, adequacy of bowel preparation regimes and the patient perspective on diagnostic measures.Methods We conducted a systematic literature search in PubMed, EMBASE and the Cochrane Register for Clinical Trials. Pooled estimates for sensitivity, specificity and the diagnostic odds ratio with their respective 95 % confidence intervals (CI) were calculated for studies providing sufficient data.Results Of 840 initially identified studies, 13 were included in the systematic review and up to 9 in the meta-analysis. The pooled sensitivities and specificities for polyps ≥ 6 mm were 87 % (95 % CI: 83 %–90 %) and 87 % (95 % CI: 76 %–93 %) in 8 studies, respectively. For polyps ≥ 10 mm, the pooled estimates for sensitivities and specificities were 87 % (95 % CI: 83 %–90 %) and 95 % (95 % CI: 92 %–97 %) in 9 studies, respectively. A patients’ perspective was assessed in 31 % (n = 4) of studies, and no preference of CCE over OC was reported. Bowel preparation was adequate in 61 % to 92 % of CCE exams.Conclusions CCE provides high diagnostic accuracy in an adequately cleaned large bowel. Conclusive findings on patient perspectives require further studies to increase acceptance/adherence of CCE for CRC screening.